Electroplex as a New Concept of Universal Host for Improved Efficiency and Lifetime in Red, Yellow, Green, and Blue Phosphorescent Organic Light‐Emitting Diodes. Issue 2 (1st December 2017) - Song, Wook; Lee, Jun Yeob; Cho, Yong Joo; Yu, Hyeonghwa; Aziz, Hany; Lee, Kang Mun
Abstract: A new concept of host, electroplex host, is developed for high efficiency and long lifetime phosphorescent organic light‐emitting diodes by mixing two host materials generating an electroplex under an electric field. A carbazole‐type host and a triazine‐type host are selected as the host materials to form the electroplex host. The electroplex host is found to induce light emission through an energy transfer process rather than charge trapping, and universally improves the lifetime of red, yellow, green, and blue phosphorescent organic light‐emitting diodes by more than four times. Furthermore, the electroplex host shows much longer lifetime than a common exciplex host. This is the first demonstration of using the electroplex as the host of high efficiency and long lifetime phosphorescent organic light‐emitting diodes. Abstract : A new concept of host, electroplex host, is developed for high efficiency and long lifetime phosphorescent organic light‐emitting diodes. The electroplex host is found to induce light emission through an energy transfer process and universally improves the lifetime of red, yellow, green, and blue phosphorescent organic light‐emitting diodes by more than four times.